Elexacaftor-Tezacaftor-Ivacaftor Treatment Reduces Abdominal Symptoms in Cystic Fibrosis-Early results Obtained With the CF-Specific CFAbd-Score - Mainz, Jochen G.; Zagoya, Carlos; Polte, Louise; Naehrlich, Lutz; Sasse, Lenny; Eickmeier, Olaf; Smaczny, Christina; Barucha, Anton; Bechinger, Lilith; Duckstein, Franziska; Kurzidim, Ludwik; Eschenhagen, Patience; et al. (Frontiers in Pharmacology, 2022)
Background: The novel and highly effective CFTR modulator combination of elexacaftor-tezacaftor-ivacaftor (ETI) has been shown to improve lung function and body weight in people with Cystic Fibrosis (pwCF) carrying a F508del mutation. However, the impact of these modulators on gastrointestinal (GI) symptoms is relatively unknown. Therefore, the CFAbd-Score was developed and validated following FDA recommendations for development of a PROM including focus groups, multidisciplinary CF specialists, people with CF and their families. The aim of this study was to assess effects of ETI on GI symptoms using the CFAbd-Score. Methods: Gastrointestinal symptoms were prospectively assessed in pwCF using the CFAbd-Score before and up to 24 weeks during therapy. The CFAbd-Score was also administered to a healthy control (HC) group. The one-sided questionnaire includes 28 items grouped in five domains. Data analysis included calculation of scores with a weighting tool, developed according to FDA recommendations. Results: A total of 107 pwCF attended in four CF centres in Germany and four centres in the UK completed the CFAbd-Score on at least two occasions. Results were compared to those obtained from the questionnaire of 45 HCs. Despite differences in demographics, age and proportion of pancreatic insufficiency between German and UK patients, analyses based on linear mixed-effects models at week 24 of ETI therapy revealed that estimated marginal means (EMMs) of total CFAbd-Scores significantly reduced (mean±SE: 14.9±1.2→10.6±1.4; p<0.01). Also EMMs of all five domains significantly declined (“pain” 16.3±1.6→10.2±2.3, “GERD” 15.8±1.8→8.2±1.9, “disorders of bowel movement” 20.9±1.5→16.0±1.7, “disorders of appetite” 7.9±1.1→2.6±1.1 and “quality of life impairment” 10.1±1.92→3.9±1.9). However, during 24 weeks, CF participants’ symptoms mostly, still did not reach the reference levels of HCs. Discussion: Using the CFAbd-Score, the first PROM specifically developed for assessment of CF-related abdominal symptoms, we demonstrate comprehensive improvements in GI symptoms after initiation of the highly effective modulator therapy ETI.